Hubungan Kompetensi Sintaksis dan Kemampuan Menulis Kalimat Efektif dalam Karangan Argumentasi Siswa Kelas X SMA Negeri 1 Lengayang - Sari, Syafitri Nila; Emidar, Emidar; Noveria, Ena (Universitas Negeri Padang, 2012)
The purposes of the study were to discribe the relation syntax competention and writed efective sentence in argumentation composition skill students class ten high school country one Lengayang.Â The Subject of the study were students class ten high school country one Lengayang 2012/2013 (290 peoples). The sampelÂ taked used random sampling tekhnik were 150 % from population (42 peoples). The data were colected by objective test and worked test. The data analicist by description and the process by used corelation product moment with ten scale. The conclusion of the study were (1) mean syntax competention which writed by students were enougt kualification (C) with value 62,67; (2) mean writed efective sentence in argumentation composition werw enougt kualification (C) with value 65,5; (3) there were relation between syntax competention and writed efective sentence in argumentation composition skill students class ten high school country one Lengayang at freedom degree (dk) n-2 and significant level 5%.